The Routledge handbook on ecosocialism - Brownhill, Leigh (New York, NY : Routledge, 2022)
"Building upon the classical works that have propelled and shaped ecosocialist thinking and action and more recent political developments on the ground, the volume will provide a reference point for international work in the field, both directly political and academic. The Handbook is an essential up-to-date guide and reference not only for researchers, but also for undergraduate and graduate students in geography, environmental studies, development studies, sociology and political science, as well as for policymakers and activists, providing detailed but accessible overviews of the complex, varied dimensions of ecosocialism"--
Keywords: Ecosocialism; POLITICAL SCIENCE / Political Ideologies / Communism & Socialism; POLITICAL SCIENCE / Public Policy / Environmental Policy; SCIENCE / Earth Sciences / Geography